Analisis Kemampuan Pemecahan Masalah Matematika Ditinjau Tipe Kepribadian Ekstrovert-Introvert - Ardiani, Vebiola; Nasution, Haryati Ahda (Universitas Islam Lamongan, 2024)
This study was conducted to analyze mathematical problem solving in terms of opportunities in terms of extrovert-introvert personality types in class X of SMKN 1 Patumbak. Researchers took samples, namely class X Rpl students of SMK Negeri 1 Patumbak with a total of 35 students. Sampling is taken by purposive sampling technique, also known as consideration sampling, which is a sampling technique from the population on certain considerations. Instruments and data collection techniques were carried out, namely by distributing questionnaires, conducting interviews, and providing test instruments. From the tests conducted, it is known that students who have extroverted personalities are more enthusiastic in working on questions than students with introverted personalities. From these results it is known that students who have introverted personalities can write down answers, but are less able to explain the answers. Meanwhile, students with extroverted personalities tend to be more confident, both in writing answers and explaining answers.